Prospective Analysis of Dogs Affected with Urinary Calculi: Diagnosis and Surgical Management - Patel, Bhaminiben M; Mahla, Jalendra K; Bodala, Jay Y; Patel, Shital K; Patel, Kaushal D; Mecvan, Arnold R (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
One-year prospective study evaluated the occurrence of urinary tract affections in dogs, with a specific focus on urinary calculi, at Veterinary Clinical Complex of the College in Anand (Gujarat, India). A total of 11,525 animals were presented, among them 126 were diagnosed with urinary tract disorders. The highest incidence was observed in canines (58.73%, n=74), followed by caprines (23.81%, n=30), bovines (11.90%, n=15), and felines (5.55%, n=7). Among 74 dogs affected with urinary tract, urinary calculi were the most common condition (n=33), followed by cystitis, kidney failure, cystitis with calculi and bladder tumours. Middle aged dogs (5-10 years) showed the highest incidence of urinary calculi and Labrador Retrievers, Pomeranians and Pugs were the most commonly affected breeds. Male dogs were slightly more affected than females, although sex distribution varied between breeds. Most dogs were fed a combination of commercial and vegetarian diet compared to only vegetarian diet or non-vegetarian diet. In one year analysis it was found that urinary calculi were the most common occurrence compared to the other urinary tract affections, and it was also related to age, breed, sex, diet and water. Among 33 dogs affected with various type of urinary calculi, 6 dogs were diagnosed by imaging techniques having complete urinary obstruction or large size of the calculi in bladder or urethra, which were managed surgically by cystotomy. Rectal temperature and haemato-biochemical parameters, except BUN & creatinine, were within normal range before and after surgery. Urinalysis was a guiding force to determine nature of calculi & thereby the therapeutic management approach.